Germination, Morphological and Physiological Evaluation of Seedlings Pretreated with Colchicine in Soybean (Glycine max L) - MANGENA, Phetole (Walailak Journal of Science and Technology (WJST), 2021)
Wider genetic diversity has the potential to improve crop productivity of soybean, especially under environmental stress conditions. The pre-treatment of soybean seeds with antimitotic agents to establish improved genetic pool may also contribute to the enhancement of germination, seedling development, morpho-physiological growth and yield. In this study, 2 soybean genotypes viz. TGx1835-10E and Dundee were imbibed in solutions containing different amounts of colchicine (0.0, 0.1, 0.5 and 1 %) to evaluate the variations in germination, morphometric and physiological parameters. The seeds were imbibed for the period of 12 and 24 h before sowing for germination in plastic pots containing moistened sterile vermiculite. The variance components expressed as means, and mean percentage of total variations showed that colchicine concentration and imbibitional duration were the most important sources of variation for all traits, followed by the genotypes. Significant responses were detected for various germination parameters, seedling morphology and physiological contents such as; chlorophyll content, total phenolics, flavonoids as well as total protein and DNA content in the 2 genotypes used. HIGHLIGHTS Mutagenic pre-treatment of seeds via imbibition Germination and seedling growths of colchicine preconditioned seeds Chloroplastidic pigment analysis of pre-treated seedlings Physiological valuation of primary and secondary metabolites in grown seedlings Role of colchicine on germination, seedling development and growth of soybean plantlets GRAPHICAL ABSTRACT